Efficacy of working from home among urban professionals in Malaysia during the pandemic: The robust predictive role of mattering - Kususanto Ditto Prihadi; Edward S.Z. Lim; Kwok Chee Chan; Shirlyn M. H. Lee; Aniq Ridwan (Intelektual Pustaka Media Utama, 2021)
Past studies suggested that the sense of mattering tend to be a robust predictor of work self-efficacy, even when controlling for strong variables such as state self-esteem. This current study aimed to investigate whether the aforementioned suggested still holds among working adults who had to work from home (WFH) during the COVID-19 pandemic in Malaysia, where the government enforced movement control order (MCO), a semi-quarantine policy where individuals can only travel within 10 kilometer radius of their respective homes. We hypothesized that the state self-esteem will fully mediate the link between mattering and work self-efficacy during the period of WFH, and that trait extraversion will moderate the mediation. In the 5th week of the MCO, our data was gathered from 109 urban working adults in Malaysia who had to WFH by employing General Mattering Scale, State Self-Esteem Scale, Remote Work Self Efficacy Measure, and the extraversion facet in Big Five Inventory. The result of bootstrap analyses with 5000 samples using PROCESS Macro Model 8 suggested that state self-esteem mediated partially mediated the association of mattering and work self-efficacy among individuals at all levels of extraversion. Discussion, limitations and suggestions are provided in the end of the paper.